2014
DOI: 10.1186/1556-276x-9-536
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of the structure of large-area carbon nanotube/fuel composites on energy generation from thermopower waves

Abstract: Thermopower waves are a recently developed energy conversion concept utilizing dynamic temperature and chemical potential gradients to harvest electrical energy while the combustion wave propagates along the hybrid layers of nanomaterials and chemical fuels. The intrinsic properties of the core nanomaterials and chemical fuels in the hybrid composites can broadly affect the energy generation, as well as the combustion process, of thermopower waves. So far, most research has focused on the application of new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…We carried out additional 30 experiments using the square‐shaped SC‐BT specimen (5 × 5 mm 2 , anisotropy: 1), otherwise the identical experimental condition, and the peak voltage was significantly smaller (maximum: 0.88 V; average: 0.3 V) than that of the 1D specimen as shown in Figure S8 (Supporting Information). Hwang et al also observed the greater peak voltage for 1D substrate, compared with 2D or 3D substrates, although the materials and experimental conditions were different from this work …”
contrasting
confidence: 47%
See 2 more Smart Citations
“…We carried out additional 30 experiments using the square‐shaped SC‐BT specimen (5 × 5 mm 2 , anisotropy: 1), otherwise the identical experimental condition, and the peak voltage was significantly smaller (maximum: 0.88 V; average: 0.3 V) than that of the 1D specimen as shown in Figure S8 (Supporting Information). Hwang et al also observed the greater peak voltage for 1D substrate, compared with 2D or 3D substrates, although the materials and experimental conditions were different from this work …”
contrasting
confidence: 47%
“…Finally, electrodes were connected at both ends of the specimen using copper tapes and silver paste (DOTITE, D‐550). An exothermic chemical reaction was initiated by a hot nickel–chromium wire . The wire was Joule‐heated and immediately came into contact with the fuel mixture on one end of the specimen after turning off the power supply.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The triple‐core–shell nanostructures of TiO 2 @MnO 2 @C are designed as electrode materials for supercapacitors, and synthesized via SGCWs, which appear in the combustion of the hybrid composites, comprised of micro‐nanostructured materials and chemical fuels. As the ignition of fuels, the entire micro‐nanostructures are instantaneously exposed to a self‐propagating reaction waves along the interfaces of the materials and fuels . These interface‐driven combustion waves simultaneously induce the formation of carbon shells around the core structures for a few seconds, in an open‐air atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…When the TW was subjected to an inverse temperature gradient, the direction of charge transport oppositely changed, which resulted in negative voltage signals. Thus, various voltage signals that corresponded to the rear‐inverse peak, no inverse peak, or front‐inverse peak scenarios could be obtained, as shown in Figure S2, depending on the ignition and propagation during the combustion process 31,34 …”
Section: Resultsmentioning
confidence: 99%